Students’ Responses on The Implementation of Virtual Reality in Teaching Vocabulary - Vina Aini Salsabila; Mila Malia Shalwan (JEPAL (Journal of English Pedagogy and Applied Linguistics), 2023)
Vocabulary is one of the elements of language that is crucial. Lack of vocabulary can lead to students’ inability to listen, read, write, and speak well. The aims of this study are to investigate students’ responses on the implementation of Virtual Reality in teaching vocabulary. The participants of this study were six students in eighth grade of a Junior High School in Cianjur. This research applied a qualitative method using questionnaire as an instrument for gaining the data. The findings show that Virtual Reality was perceived variously by the students. The students declared virtual reality as a supportive device, a user-friendly application, and provision of an immersive experience which make them learn vocabulary authentically. However, the students faced some challenges during the learning process including the limitation of supportive device and the negative physical effect such as feeling dizzy and getting headache.